Pembelajaran Fasholatan sebagai Upaya dalam Meningkatkan Kemampuan Ibadah Anak melalui Metode Pembiasaan (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
TPA Asy-Syafi'i is located on Jalan Asy-syafi'i Dusun Sidomulyo Desa Cekok, Babadan, Ponorogo. Taman Pendidikan Al-Qur'an can be interpreted as an important institution besides studying at school. TPA was founded by Kiai Syamsudin who aims to form morals and Quranic personality in children. Initially, there was only one child who studied the Koran as time went by the children increased. So Kiai Syamsudin thought of establishing a TPA which is located in the At-thoyyib mosque in Cekok village. At TPA Asy-Syafi'i only tajwid reading is taught and uses the qiro'ati method. The qiro'ati method is reading the Koran which directly practices tartil reading. So that the learning in the TPA is not extensive enough. Starting from the assets owned, namely religious education and children who study the Koran at TPA are quite a lot, the cadre ship of fasholatan learning as an effort to improve children's worship skills through the habituation method is feasible to be implemented. After the training was carried out, the enthusiasm of the children and the teachers who taught was very good. The children participated in the training activities with enthusiasm. This shows the ability of the results of the evaluation that has increased. Increased ability can be known by evaluating the form of a pre-test and post-test.